THE EFFECT OF THE GUIDED INQUIRY LEARNING MODEL ON STUDENT LEARNING OUTCOMES ON PLANT STRUCTURE AND FUNCTION MATERIAL IN GRADE VIII SMP NEGERI 12 MEDAN - Ramlan Silaban; Marpaung, Fytry Vebiola; Retno Dwi Suyanti; Mariati Purnama Simanjuntak; Aristo Hardinata (Jurnal Ilmu Pendidikan Indonesia, 2025)
Abstract: The guided inquiry learning model is one of the learning models that can improve student learningoutcomes and student learning activities which is a learning model where teachers and students determineand formulate problems together, and students actively seek and find answers and draw their ownconclusions. The purpose of the study was to determine the results of science learning on the material ofPlant Structure and Function of class VIII students of SMP Negeri 12 Medan. To determine the Effect ofthe Guided Inquiry Learning Model on Student Learning Outcomes on the Material of Plant Structure andFunction in Class VIII SMP Negeri 12 Medan. This research method uses a quantitative research method.The form of research is Quasi Experimental Design. The research design is a two group design. Datacollection techniques were carried out using pre-research observations, interviews with Class VIII scienceteachers, conducting written tests on students in the form of questions, non-tests or questionnaires, observingstudent activities, and documentation in the form of research images and photos and value documents relatedto the results. Data analysis using hypothesis testing (one-sided t-test) and N-Gain testing. Based on theresults of the t-test, the obtained t-value is 4.66> t-table 2.00. This means that the results of the hypothesistest t-count are greater than t-table. Next, based on the results of the N-gain test, the increase in learningoutcomes in the control class was higher, namely 69% compared to the increase in student learning outcomesof 52%. So that the Guided Inquiry Learning Model applied to the experimental class in this study has aneffect on student learning outcomes in the material on the Structure and Function of Plants in class VIII ofSMP Negeri 12 Medan.Keywords: Learning